Customer Shopping Behavior and the Persistence of Revenues and Earnings - Jin, Hengda; Stubben, Stephen R.; Ton, Karen (The Accounting Review, 2025)
ABSTRACT Using GPS location data from customers’ mobile devices, we develop measures of customer shopping behavior intended to capture the likelihood that customers will shop again in the future, and we examine their associations with firms’ financial decisions and outcomes. We measure customers’ propensity to return using the frequency, distance, duration, and timing of their past visits to a firm’s retail locations. We find a positive association between customers’ propensity to return and the persistence of the firm’s revenues and earnings. We also find a positive association between customers’ propensity to return and the efficiency of investing and operating decisions among firms likely to incorporate customer data into their internal information systems. Our results illustrate conditions under which revenues and earnings are sustainable and when managerial decisions are consistent with insights provided by customer information. Data Availability: Data are available from the public sources cited in the text. JEL Classifications: M31; M41; G14; G31.